Spatial mapping of heat vulnerability in Abuja, the capital city of Nigeria - Joshua, Jonah Kunda (2023)
Urbanisation alters land surface features by replacing natural environments with artificial impervious surfaces (AIS). Such changes modify the thermal properties of cities, making cities more vulnerable to heat, with growing threats to human health. This study mapped the heat vulnerability for human health in Nigeria's capital, Abuja. Landsat imagery and gridded population and socioeconomic variables from the WorldPop database and demographic and health surveys were combined to develop 9 heat vulnerability indicators for a spatial mapping: maps of land surface temperature, AIS, Normalised Difference Vegetation Index, the vulnerable population comprising those aged below 14 and over 65 years, the women population, population density, poverty level, literacy rate, and dwelling quality. The attributes of each indicator were first reclassified based on their relative influence on heat vulnerability using a fundamental scale of 1 to 5, where '1' was designated very low influence and '5' indicated very high influence. The weighted overlay was used for the spatial mapping of the heat vulnerability using an expert's judgment as an input. The study's results reveal a significant relationship between AIS, LST, and NDVI (p<0.05). The association between maximum temperature and heat-related mortality was statistically significant as its p-value is less than 0.05 in all six locations of the research area, with the informal settlement having a larger correlation (r2: 0.62) than the city centre (r2:0.28). 12% and 30% of the map areas are high and very highly heat-vulnerable, while 27% are moderately heat-vulnerable. Low and very low vulnerability regions occupied 23% and 8% of the map. The projections of heat vulnerability to the middle and end of the 21st century using temperature projections from 5 selected CMIP6 GCMs for the low and high forcing scenarios, and demographic and socioeconomic variables show a consistent increase in spatial patterns and temporal trends of the heat vulnerability compared to the heat vulnerability map at present. The study's findings indicate the existence of informal settlements within the high and very high heat-vulnerability areas. Most urban areas with surrounding vegetation cover are moderately vulnerable to heat. Low or very low heat vulnerability exists in regions with water bodies and natural cover, supporting the importance of Blue-Green infrastructures in heat reduction. The heat vulnerability projections could considerably influence heat-related risk in the future, highlighting the need for risk assessments incorporating long-term climatic and socioeconomic indicators. The heat vulnerability maps produced by this research have the potential to serve as a baseline for long-term climate resilience and adaptation plan. The thesis contributes to developing a better understanding of the impacts of extreme temperatures on human health.